Shungite paste electrodes: Basic characterization and initial examples of applicability in electroanalysis - Bártová, Michaela; Bartoš, Martin; Švancara, Ivan; Sýs, Milan (MDPI, 2024)
This article introduces a new type of carbon paste electrode prepared from black raw shungite. In powdered form, this carbonaceous material was mixed with several nonpolar binders. The resulting shungite pastes were microscopically and electrochemically characterized. Mixtures of several pasting liquids with different contents of shungite powder were tested to select the optimal composition and compared with other types of carbon paste-based electrodes made of graphite and glassy carbon powder. In terms of physical and mechanical properties, shungite paste electrodes (ShPEs) formed a composite mass being like dense pastes from glassy carbon microspheres, having harder consistency than that of traditional graphitic carbon pastes. The respective electrochemical measurements with ShPEs were based on cyclic voltammetry of ferri-/ferro-cyanide redox pairs, allowing us to evaluate some typical parameters such as electrochemically active surface area, double-layer capacitance, potential range in the working media given, heterogeneous rate constant, charge-transfer coefficient, exchange current density, and open-circuit potential. The whole study with ShPEs was then completed with three different examples of possible electroanalytical applications, confirming that the carbon paste-like configuration with powdered shungite represents an environmentally friendly (green) and low-cost electrode material with good stability in mixed aqueous-organic mixtures, and hence with interesting prospects in electroanalysis of biologically active organic compounds. It seems that similar analytical parameters of the already established variants of carbon paste electrodes can also be expected for their shungite analogues.
Šungitové pastové elektrody: Základní charakteristika a počáteční příklady použitelnosti v elektroanalýze
Keywords: Shungite; carbon pastes; Microscopic study; Electrochemical characterization; Reaction kinetics; Electroanalytical applications; Šungit; Uhlíkové pasty; Mikroskopické studie; Elektrochemická charakterizace; Reakční kinetika; Elektroanalytické aplikace